Development of Unconventional Reservoirs - Rezaee, Reza (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The need for energy is increasing and but the production from conventional reservoirs is declining quickly. This requires an economically and technically feasible source of energy for the coming years. Among some alternative future energy solutions, the most reasonable source is from unconventional reservoirs. As the name “unconventional” implies, different and challenging approaches are required to characterize and develop these resources. This Special Issue covers some of the technical challenges for developing unconventional energy sources from shale gas/oil, tight gas sand, and coalbed methane.